The BRAF and NRAS mutation prevalence in dermoscopic subtypes of acquired naevi reveals constitutive mitogen‐activated protein kinase pathway activation. (22nd January 2018) - Tan, J.M.; Tom, L.N.; Jagirdar, K.; Lambie, D.; Schaider, H.; Sturm, R.A.; Soyer, H.P.; Stark, M.S.
Summary: Most people have a few brown spots on their skin known as melanocytic naevi or moles. Moles are harmless but can occasionally transform into a potentially lethal tumour called malignant melanoma. Dermatologists recognise different types of mole from their appearance under a magnifying lens (dermatoscope). Broadly speaking: "globular" naevi appear early in life and may transform into melanoma; "reticular" naevi develop in adults and may be associated with melanoma arising at a site where no mole was present; reticular naevi with "peripheral globules" (PG) are growing but not malignant. Mutations (mistakes) in BRAF and NRAS genes occur in both benign and cancerous moles (malignant melanoma). These genes are components of the MAPK pathway which is important in tumour development. To try to clarify the role of these genes, these researchers in Australia looked for a relationship between dermoscopic appearance and NRAS and BRAF mutations in benign moles. They examined, dermoscopically, 40 acquired (non‐congenital) moles in 27 people then removed them for analysis. Under the microscope, disordered cell structure was observed in most reticular naevi but rarely in globular and PG naevi. Using a new, highly sensitive technique ("droplet digital PCR") able to detect mutations in single cells, they found that most globular and all PG naevi had a BRAF mutation whereas reticular naevi had either BRAF or NRAS mutations. They conclude that all moles harbour mutations in MAPK genes, confirming a fundamental role for the MAPK pathway in the development of melanocytic naevi as well as melanoma. Abstract : Linked Article: Tan et al. Br J Dermatol 2018; 178 :191–197